Fixed Point Curve for Weakly Inward Contractions and Approximate Fixed Point Property (Analysis in Theory and Applications, 2013)
In this paper, we discuss the concept of fixed point curve for linear interpolations of weakly inward contractions and establish necessary condition for a nonexpansive mapping to have approximate fixed point property.